Evaluasi Critical Success Factors terhadap Keberhasilan Proyek Konstruksi menggunakan Metode Analytical Hierarchy Process (Studi Kasus: Proyek Gedung IME UNSOED) (Indonesian Journal of Civil Engineering Study, 2026)
Construction building projects play an important role in supporting infrastructure development; however, their implementation often faces delays, cost overruns, and quality deterioration. Therefore, a comprehensive evaluation of the factors influencing project success is required. Critical Success Factors (CSFs) are key factors conditions, characteristics, or variables that directly affect a project’s success because they determine what must be managed effectively to achieve project objectives. This study was conducted through interviews and questionnaire surveys administered to project stakeholders. The data were analyzed using the Analytical Hierarchy Process (AHP) to obtain priority weights for each aspect and factor. The results identify seven aspects and twenty-three factors that influence the success of the Integrated Medical Education (IME) Building Project at UNSOED. The quality aspect has the highest priority, with a weight of 0.192. The five most dominant factors are the effectiveness of schedule control and monitoring (0.0744), early risk identification (0.0684), the quality control system and quality documentation (0.0681), compliance with technical quality standards (0.0644), and the level of user satisfaction (0.0593). These findings indicate that the dominant factors should receive primary attention in project management particularly those related to quality, time, and risk management in order to improve overall project success.
Keywords: Analytical Hierarchy Process; Cost Overruns; Early Risk Identification; Quality Aspect; User Satisfaction